Comparative immunological study of Plasmodium knowlesi infections in humans and macaques: Insights into cytokine dynamics - Mohammad Faruq Abd Rachman Isnadi; Yean Kong Yong; Matthew J. Grigg; Symphorosa Sipangkui; Ping‑Chin Lee; Nor Afizah Nuin; Angelica Fiona Tan3; Paul Molius; Augustine Tuuga; Jum Rafiah Abd Sukor; Giri Rajahram; Sylvia Daim; et al. (BioMed Central Ltd., 2025)
Plasmodium knowlesi, a simian malaria parasite endemic to Southeast Asia, is transmitted from macaques to humans via mosquitoes and has seen a surge due to human encroachment into macaque habitats. While the primary host, Macaca fascicularis, can regulate P. knowlesi and alleviate disease symptoms, infected humans face a different scenario. A study was conducted in Sabah, Malaysia to compare the effects of parasite genomic DNA (gDNA) and host (both human and macaques) mitochondrial DNA (mt DNA) release on cytokine profiles in humans and macaques infected with P. knowlesi. Methods Blood samples from 30 Plasmodium knowlesi‑infected individuals and 30 healthy controls, along with serum samples from 35 wild macaques, were analyzed using PCR and immunological assays. Nested PCR and real‑time PCR were performed on macaque blood samples to confirm mono‑infection with P. knowlesi. Parasite genomic DNA (gDNA) levels were quantified via qPCR. Additionally, the concentrations of six cytokines—TNF, IFNγ, IL‑1β, IL‑4, IL‑6, and IL‑10—were measured in the samples. Results Parasitemia levels, determined through microscopy method, exhibited strong correlations with parasite gDNA. Notably, the infected macaques displayed significantly higher parasite gDNA and mt DNA levels compared to humans. Cytokine analysis unveiled IL‑10 dominance in humans, positively associated with parasite gDNA, while macaques showed IL‑6 dominance unrelated to parasite gDNA. Despite lower parasite gDNA levels, patients exhibited a higher IL‑10/TNF ratio, indicative of disease severity. Conclusions These results suggestively highlight variations in immune responses between two distinct hosts in two different phases of infection: human (acute infection) and macaque (presumed chronic infection) hosts. The correlations and interplay between parasite gDNA, host’s mt DNA (both human and macaques) and cytokine levels observed in this study further emphasizing the need for further research to comprehensively understand P. knowlesi pathogenesis.